If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + 5 + 6v = 1 + 5v + 3 Combine like terms: -4 + 5 = 1 1 + 6v = 1 + 5v + 3 Reorder the terms: 1 + 6v = 1 + 3 + 5v Combine like terms: 1 + 3 = 4 1 + 6v = 4 + 5v Solving 1 + 6v = 4 + 5v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-5v' to each side of the equation. 1 + 6v + -5v = 4 + 5v + -5v Combine like terms: 6v + -5v = 1v 1 + 1v = 4 + 5v + -5v Combine like terms: 5v + -5v = 0 1 + 1v = 4 + 0 1 + 1v = 4 Add '-1' to each side of the equation. 1 + -1 + 1v = 4 + -1 Combine like terms: 1 + -1 = 0 0 + 1v = 4 + -1 1v = 4 + -1 Combine like terms: 4 + -1 = 3 1v = 3 Divide each side by '1'. v = 3 Simplifying v = 3
| 3(c+4)=5+2c | | (4x-1)+(2x+1)=8x-4 | | 3i^2+15/6-3i | | 7(x-1)=6x | | x^2+15/6-x | | 3z+3-z=10+z-5 | | 36=2(3.14)r | | 3x-13=2x | | 7g+1-5g=-8 | | -X^2-12X-20=0 | | 73.14/23 | | x/3+12/1=-x/3 | | -[5z-(15z+6)]=6+(9z+0) | | (-11-16)+5= | | 5x/7+12/7=-13/7 | | -4(y+2)=-3y-1 | | 1-6x-13= | | -4(x-6)=-4x+24 | | ln(3x+6)=3 | | 41.5/5 | | 5x+2=8x-4x | | 3y+7x=13 | | 5x+4+4x=31 | | 10.98/3.4 | | x+x+1=x+2+24 | | y=x^2+8x-11 | | 35/8x12/15 | | -1.2r=6.0 | | x^2+8x-11=y | | 4=2y+105 | | 4=2y+70 | | -12r=6.0 |